Optimization And Mass Transfer Simulation Of Remazol Brilliant Blue R Dye Adsorption Onto Meranti Wood Based Activated Carbon - Mohamad Firdaus Mohamad Yusop; Muhammad Azan Tamar Jaya; Iylia Idris; Ahmad Zuhairi Abdullah; Mohd Azmier Ahmad (Elsevier, 2024)
Indexed by WOS/ERA